Defining Social Inclusion for People with Disabilities in Governance: Scoping and Thematic Literature Review - Nurhaeni, Ismi Dwi Astuti; Wiratama, Prama; Putri, Intan Sani; Nurdin, Asbiyal; Mulyadi, Asal Wahyuni Erlin; Haryani, Tiyas Nur; Sudibyo, Desiderius Priyo (UI Scholars Hub, 2023)
Consensus on a precise definition of social inclusion for people with disabilities remains elusive. This study aims to systematically review the definition of Social Inclusion for People with Disabilities in Governance (SIPDG) based on the related literature and offer basic theoretical insight into what might be considered relevant for establishing a definition of SIPDG. A scoping review was conducted with a qualitative synthesis of literature from SCOPUS. Articles were identified by final keywords of